On God's Existence. - Pasquini, John J. (Hamilton Books, 2016)
Philosophy and the advances in cosmology, neurology, molecular biology, and the social sciences have made the convincing and converging arguments for God's existence more probable than ever in history. On God's Existence is concise summary of these arguments as well as new arguments inspired by the advances of the sciences.